2019
DOI: 10.1109/tnet.2019.2953921
|View full text |Cite
|
Sign up to set email alerts
|

Network Topology Mapping From Partial Virtual Coordinates and Graph Geodesics

Abstract: For many important network types (e.g., sensor networks in complex harsh environments and social networks) physical coordinate systems (e.g., Cartesian), and physical distances (e.g., Euclidean), are either difficult to discern or inapplicable. Accordingly, coordinate systems and characterizations based on hop-distance measurements, such as Topology Preserving Maps (TPMs) and Virtual-Coordinate (VC) systems are attractive alternatives to Cartesian coordinates for many network algorithms. Herein, we present an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Specifically, we will utilize BMC technique to capture and characterize network topology of social networks such as Facebook, Arxiv, and Enron e-mail. We will also utilize BMC scheme to map network topology of 2-D and 3-D sensor networks from partial virtual coordinates to graph geodesics [28]. In addition, we are interested in DR of collective motion such as schools of fish and flocks of birds.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we will utilize BMC technique to capture and characterize network topology of social networks such as Facebook, Arxiv, and Enron e-mail. We will also utilize BMC scheme to map network topology of 2-D and 3-D sensor networks from partial virtual coordinates to graph geodesics [28]. In addition, we are interested in DR of collective motion such as schools of fish and flocks of birds.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that the approach that we call Topological is widespread; it is used in various areas where communication networks are established [30] since it is convenient to study the topology properties of networks using graph theory (for example, as in [30,31], dedicated to supercomputers, or as in [32,33], dedicated to decision-making in communication networks). Network information transmission delay is related to the diameter and MPL of the graph, while network fault tolerance is connected to the connectivity of the graph [34][35][36]. In the following sections, we will rely on the Topological approach, considering NoC and routing algorithms in it at a high level of its topology and abstracting from the NoC physical implementation for simplicity.…”
Section: Topological Approachmentioning
confidence: 99%
“…diameter and MPL of the graph, while network fault tolerance is connected to the connectivity of the graph [34][35][36]. In the following sections, we will rely on the Topological approach, considering NoC and routing algorithms in it at a high level of its topology and abstracting from the NoC physical implementation for simplicity.…”
Section: Circulant Versus Mesh and Torusmentioning
confidence: 99%
“…We compare the performance of HDA against a generalized version of the benchmark low-rank matrix completion (LMC) technique given in [18]. We presented in our previous work [28,29], that LMC exhibit superior performance in topology recovery of both partially observed directed graphs and partially observed uncorrected graphs. In a similar vein, we have also shown that LMC methods have significant performance in reconstruction of fragmented trajectories because the coordinate matrix representing agents' trajectories of collective motion is often low-rank due to mutual interactions and dependencies between the agents [7].…”
Section: Low-rank Matrix Completionmentioning
confidence: 99%